A methodology for the identification of strategic technological competences: An application in the sheet metal equipment industry. (June 2017) - Santos, Cláudio; Araújo, Madalena; Correia, Nuno
Highlights: A methodology for considering events' relationships in Delphi surveys is proposed. The methodology was implemented in a sheet metal equipment manufacturer. The methodology supports the identification of strategic technology competences. Application promotes a homogenous view of the drivers of technologies' diffusion. Abstract: This paper proposes a technology foresight methodology based on the development of a complementary approach to the Delphi method that enables the identification of strategic technological competences, and presents its application in a sheet metal processing equipment manufacturer. The proposed methodology takes into consideration synergies between future events through a modified QFD matrix, and the application involved a panel of experts from industry and academia. The proposed methodology can benefit organizations by promoting a homogeneous perspective on existing relationships between external drivers and technology diffusion. This study contributes for the understanding of the links between foresight and technology strategy formulation. Further implementations in industrial environments should be performed to refine the methodology and increase the confidence level on the expected results that these findings can signify.